Pengaruh Kebijakan Dividen, Likuiditas, dan Solvabilitas terhadap Nilai Perusahaan Perbankan di BEI Periode 2021-2023 - Christian, Iwan; Ahmad Dwi Mubarok; Hussain, Abrar; Saputra, Achmad Andika; Wildan, Alfan Hoirul; Pratama, Andika Rizki; Aprillia, Dhini; Ahkam, Aufa Muhammad (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to examine and analyze the influence of dividend policy, liquidity, and solvency on the firm value of banking companies listed on the Indonesia Stock Exchange (IDX) during the observation period of 2021-2023. The type of research used is quantitative research. The population in this study consists of banking companies listed on the Indonesia Stock Exchange, totaling 47 companies. The sampling technique used is purposive sampling, resulting in a sample of 16 banking sector companies that meet specific criteria. The data analysis technique employed is multiple linear regression analysis using the Eviews version 9 data processing program. The results show that dividend policy has a positive and have no effect on firm value, while the liquidity and solvency variables indicate a negative and have no effect on firm value.